Transmission image : visual translation and cultural agency - Mersmann, Birgit; Schneider, Alexandra (Cambridge Scholars, 2009)
Transmission Image: Visual Translation and Cultural Agency offers a challenging survey of the burgeoning debate about visual culture in a global perspective. Bringing together scholarly perspectives on places ranging from China and India to Nigeria, and from the Philippines and Syria to Germany, this volume proposes a truly global outlook on the study of visual culture in both a contemporary and an historical perspective. Addressing key theoretical issues, the contributors cover a wide range of art forms and visual media, highlighting the complex cultural codification of images and its impact on the study of visual culture and globalization.